Financial development and income inequality in Pakistan and Malaysia / Farhanna Shafiqka Kamarudin - Kamarudin, Farhanna Shafiqka (2018)
Most of country that well develop usually based on their well-being financial development. Financial development is government and private sector development strategy to stimulate economic growth in term aligned with reduction of poverty. Income inequality means the effect from the unbalance household income that invite to the gap between the rich and poor. Financial development that consist four components such as domestic credit to private sector (% of GDP) as indicator for financial development, real GDP per capita, consumer price index and trade. This study aims to investigate the relationship between financial development and income inequality in Pakistan and Malaysia by using Gini coefficient as indicator for income inequality. The data from this study collected from secondary data and quantitative approach which is times series and multiple regression model represented by the ordinary least square (OLS). The dependent variable for this study is income inequality (GINI) and for independent variables are financial development (FD), real GDP per capita (RGDP), consumer price index (CPI) and trade. The sample of 2 countries was chosen with the time period 30 years from 1987 until 2016. The data will be relied on yearly basis that obtain from World Development Indicator.